Fiscal Discipline in WAEMU : Rules, Institutions, and Markets - Hitaj, Ermal; Kursat Onder, Yasin (Washington, D.C. : International Monetary Fund, 2013)
This paper gauges the scope for market discipline and the effectiveness of the regional surveillance framework in the West African Economic and Monetary Union (WAEMU). The paper finds that the responsiveness of sovereign bond rates to governments' fiscal behavior in the regional financial market remains limited. In addition, the paper examines the effectiveness of fiscal rules and institutions in an environment where financial markets fall short of exerting a significant disciplining effect on governments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet